2019
DOI: 10.3847/1538-4357/ab4e96
|View full text |Cite
|
Sign up to set email alerts
|

Revised Simulations of the Planetary Nebulae Luminosity Function

Abstract: We describe a revised procedure for the numerical simulation of planetary nebulae luminosity functions (PNLF), improving on previous work (Méndez & Soffner 1997). The procedure now is based on new H-burning post-AGB evolutionary tracks (Miller Bertolami 2016). For a given stellar mass, the new central stars are more luminous and evolve faster. We have slightly changed the distribution of the [O III] 5007 intensities relative to those of Hβ and the generation of absorbing factors, while still basing their numer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…They found that models of the four M PNe in their sample indicated progenitor masses clustered at the "knee" of the 1.5 M M3B16 track; these stars, according to Gesicki et al (2018), can spend ∼ 1000 years at the bright end of the PNLF. Their average remnant mass is 0.574 M , which, interestingly, agrees with the 0.58 M "maximum final mass" derived from PNLF simulations by Valenzuela et al (2019). However, Davis et al (2018) analyzed a sample of bulge PNe in M31 and concluded that after accounting for the dimming effects of circumstellar dust, the brightest objects at the observed PNLF cutoff are in fact up to 1 mag brighter than the canonical M value (implying even more massive central stars 0.66 M ).…”
Section: The Planetary Nebula Luminosity Functionsupporting
confidence: 86%
See 1 more Smart Citation
“…They found that models of the four M PNe in their sample indicated progenitor masses clustered at the "knee" of the 1.5 M M3B16 track; these stars, according to Gesicki et al (2018), can spend ∼ 1000 years at the bright end of the PNLF. Their average remnant mass is 0.574 M , which, interestingly, agrees with the 0.58 M "maximum final mass" derived from PNLF simulations by Valenzuela et al (2019). However, Davis et al (2018) analyzed a sample of bulge PNe in M31 and concluded that after accounting for the dimming effects of circumstellar dust, the brightest objects at the observed PNLF cutoff are in fact up to 1 mag brighter than the canonical M value (implying even more massive central stars 0.66 M ).…”
Section: The Planetary Nebula Luminosity Functionsupporting
confidence: 86%
“…Though we still do not entirely understand its foundations, the bottom line is that the PNLF promises to remain a valuable tool. Studies like those by Gesicki et al (2018), Valenzuela et al (2019), and Bhattacharya et al (2021 demonstrate the significant potential of the PNLF to study star formation history and stellar populations. As a distance indicator, the PNLF is benefitting from new instrumental capabilities and analysis techniques that provide increasingly accurate and deeper measurements of PNe in distant galaxies.…”
Section: The Planetary Nebula Luminosity Functionmentioning
confidence: 95%
“…Gesicki et al (2018) further explored the effect of star formation history and stellar population age on the bright cut-off of the PNLF of a detected PNe population. Together with the recent work of Valenzuela et al (2019), these studies finally overcome the initial difficulties of obtaining M * 5007 PNe in old stellar populations with mostly solar-mass star progenitors (e.g. Marigo et al 2004).…”
Section: Pnlfmentioning
confidence: 87%
“…For instance, the actual presence of bright PNe in old, passively evolving systems is a long-standing problem (Marigo et al 2004;Ciardullo 2005) that only recent theoretical development has started to address (e.g. Gesicki et al 2018;Valenzuela et al 2019). Likewise, both the origin of the PNLF bright cut-off (e.g.…”
Section: Introductionmentioning
confidence: 99%